Comparative evaluation and analysis of DNA N4-methylcytosine methylation sites using deep learning - Ju, Hong; Bai, Jie; Jiang, Jing; Che, Yusheng; Chen, Xin (Frontiers in Genetics, 2023)
DNA N4-methylcytosine (4mC) is significantly involved in biological processes, such as DNA expression, repair, and replication. Therefore, accurate prediction methods are urgently needed. Deep learning methods have transformed applications that previously require sequencing expertise into engineering challenges that do not require expertise to solve. Here, we compare a variety of state-of-the-art deep learning models on six benchmark datasets to evaluate their performance in 4mC methylation site detection. We visualize the statistical analysis of the datasets and the performance of different deep-learning models. We conclude that deep learning can greatly expand the potential of methylation site prediction.